Promotor Hypomethylation Mediated Upregulation of miR-23b-3p Targets PTEN to Promote Bronchial Epithelial-Mesenchymal Transition in Chronic Asthma - Guo, Yimin; Yuan, Xiaoqing; Hong, Luna; Wang, Qiujie; Liu, Shanying; Li, Zhaolin; Huang, Linjie; Jiang, Shanping; Shi, Jianting (Frontiers in Immunology, 2022)
Chronic asthma is characterized by airway inflammation and irreversible airway remodeling. Epithelial-mesenchymal transition (EMT) is a typical pathological change of airway remodeling. Our previous research demonstrated miR-23b inhibited airway smooth muscle proliferation while the function of miR-23b-3p has not been reported yet. Besides, miRNA is regulated by many factors, including DNA methylation. The function of miR-23b-3p and whether it is regulated by DNA methylation are worth exploring. Balb/c mice were given OVA sensitization to develop the asthmatic model. Expression of miR-23b-3p and EMT markers were measured by RT-qPCR, WB and immunohistochemistry (IHC). DNA methylation was detected by methylation-specific PCR (MSP) and the MassARRAY System. Asthmatic mice and TGF-β1-stimulated bronchial epithelial cells (BEAS-2B) showed EMT with increased miR-23b-3p. Overexpression of miR-23b-3p promoted EMT and migration, while inhibition of miR-23b-3p reversed these transitions. DNA methyltransferases were decreased in asthmatic mice. MSP and MassARRAY System detected the promotor of miR-23b showed DNA hypomethylation. DNA methyltransferase inhibitor 5’-AZA-CdZ increased the expression of miR-23b-3p. Meanwhile, PTEN was identified as a target gene of miR-23b-3p. Our results indicated that promotor hypomethylation mediated upregulation of miR-23b-3p targets PTEN to promote EMT in chronic asthma. miR-23b-3p and DNA methylation might be potential therapeutic targets for irreversible airway remodeling.